Diffusion-limited reactions in dynamic heterogeneous media - Yann Lanoiselée (Nature Portfolio, 2018)
“Diffusing diffusivity” concept has been recently put forward to account for rapid structural rearrangements in soft matter and biological systems. Here the authors propose a general mathematical framework to compute the distribution of first-passage times in a dynamically heterogeneous medium.